'I call it stinkin' thinkin'': A qualitative analysis of metacognition in people with chronic low back pain and elevated catastrophizing. Issue 3 (3rd April 2017) - Schütze, Robert; Rees, Clare; Slater, Helen; Smith, Anne; O'Sullivan, Peter
Abstract : Objectives: Pain catastrophizing is widely studied in quantitative pain research because of its strong link with poor pain outcomes, although the exact nature of this construct remains unclear. Focusing on its ruminative dimension, the present qualitative study aimed to explore a nascent aspect of pain catastrophizing – metacognition – by documenting people's attitudes towards rumination and examining how these metacognitions might influence the course it takes. Design: Qualitative interview study. Methods: Semi‐structured interviews were conducted in a tertiary care setting with 15 adults experiencing chronic (≥6 months) low back pain who scored highly (≥30) on the Pain Catastrophising Scale. Transcripts were analysed using interpretative phenomenological analysis. Results: The first aim of documenting pain metacognitions revealed both positive (e.g., 'thinking helps me to cope') and negative (e.g., 'rumination is uncontrollable') attitudes towards pain rumination. These were often held simultaneously, creating internal conflict. The second aim of exploring the influence of metacognition on rumination showed that both negative and positive metacognitions could fuel perseverative thinking. However, more nuanced negative metacognitions (e.g., 'worry is pointless') could help to end episodes of rumination by motivating the use of concrete problem‐solving or active coping behaviours. Conclusions: While most participants described pain rumination as uncontrollable and harmful, dwelling on pain could be helpful when focused on tangible and solvable problems, thereby translating into adaptive coping behaviours that eventually interrupt rumination. Future treatments may be more effective if they are based on individualized formulations of pain catastrophizing that focus on its perseverative nature and implicit function. Statement of contribution What is already known on this subject? Chronic pain affects one in five people, and psychological coping responses are key targets within gold standard biopsychosocial interventions. People who have elevated pain catastrophizing tend to have worse pain outcomes, including increased pain, disability, and emotional distress. What people believe about their own thinking (i.e., their metacognitions) influences how much they worry or ruminate. What does this study add? This is the first qualitative study exploring metacognitions in people with chronic pain and the first to target a purposive sample of people with elevated pain catastrophizing. People with elevated pain catastrophizing often see rumination as uncontrollable and harmful but may simultaneously believe it helps them to solve problems or feel prepared for future threats. Pain catastrophizing is not a stable and enduring trait but fluctuates both within and across individuals in response to pain, context, metacognitive beliefs about rumination, and coping behaviours.